General Motors Building, New York World's Fair (Curt Teich & Co.)
In keeping with the World's Fair theme of "Building the World of Tomorrow," the General Motors Exhibit presents a conception of future motor traffic regulations and super-highways. ""Highways and Horizons."" By means of a continuous escalator, visitors seated in comfortable moving chairs travel over the super-highways of tomorrow. The tour is climaxed by a full-size street intersection, showing the architecture, motor traffic and pedestrian facilities of the future. Norman Bel Geddes is the designer, and the architect is Albert Kahn, Inc.